Indonesia's Economic Diplomacy in Facing Red (Renewable Energy Directive) and European Union Palm Oil Policy - Isnan, Edyana (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
This study aims to examine Indonesia's economic diplomacy efforts in dealing with the Renewable Energy Directive (RED) and palm oil policies in the European Union. This economic diplomacy effort is a step to deal with the impact caused by policies implemented by the European Union. The method used is descriptive qualitative with data collection techniques in the form of literature review related to the problem under study. This literature includes books, journals, written reports, articles, news collections on the internet, and documents related to the object of research. Furthermore, the data analysis technique used is qualitative. The results found that in dealing with the policy, Indonesia used commercial diplomacy by cooperating with stakeholders to form FoKSBI, as well as making ISPO policies and suing the European Union regarding its claims